A strategy for a more efficient use of technology assets the Chedlink project - Isidro, Ariel E.; Zamora, Elvira A. (Quezon City University of the Philippines Diliman, 2004)
The Commission on Higher Education (CHED), a government policy giving body in the Higher Education sector has started to implement an Information System Plan, as adherence to the requirements for government agencies under the Office of the President. Project CHEDLINK was submitted to, reviewed and approved by the National Computer Center. The project involves interconnecting the CHED Central Office (CHEDCO) and CHED Regional Office (CHEDROs). In July 2002, the local area network connection between the divisions of the Central Office was completed. Similarly, a local area network was setup in each of the Regional Offices. However, the newly set-up infrastructure has not been fully utilized yet and the benefit from the network has not been gained, according to some users. For this reason, this project was conceptualized. This project intends to examine the IT competence of the Commission, formulate training strategies and identify application programs to be used by the employees to simplify daily job assignments, thus, reversing the negative impressions on the system. The project commenced during the first semester of academic year 2003-2004 and was completed on January 30, 2004. The CHED Executive Director signed the memorandum requesting all employees to accomplish the ICT Survey Form. This memorandum, attached to the forms was distributed to all employees and later collected. Most computer users in the Commission accomplished the form. A customized computer program was developed for tallying, processing, and generating the reports. The result of the survey shows varied competency levels for different categories, but mostly fell somewhere in the middle of the scale. Chi-square tests and t-tests were used to further examine extreme results. Probing interviews were also conducted with some respondents. Finally, recommendations were formulated based on the study results.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Philippines. Commission on Higher Education; Local area networks (Computer networks) -- Planning -- Philippines; Network analysis (Planning) -- Philippines